(untitled) (Bangladesh Journal of Plant Taxonomy, 2013)
This paper presents the phenology of seven taxa of the genus Magnolia L., pollen biology on germination and storage conditions, seed productivity, germinating ability of seeds and its dependence on stratification and germination conditions. It has been found that M. kobus DC, M. kobus var. boreales Sarg., M. obovata Thurb., M. officinalis Rehd. et Wils., M. salicifolia (Sieb. et Zucc.) Maxim., M. sieboldii K. Koch. and M. tripetala L. in cultivated condition produce pollen at a low viability rate (9.4 - 31.7%). Real seed productivity of the taxa being studied is less than their potential productivity. However, M. obovata, M. officinalis and M. tripetala are characterized by high seed germinating ability, up to 94%. Optimal germination conditions for seeds of M. tripetala, M. officinalis and M. obovata require protected ground (greenhouse) and stratification at 4ºC during 30 days. The high germinating ability of M. sieboldii seeds in the open ground is explained by stratification duration and temperature required for this species. Sarcotesta effects on higher seed germinating ability have been observed in M. obovata only. DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17390 Bangladesh J. Plant Taxon. 20(2): 163-170, 2013